The Dimensions of Industrial Growth in Tamil Nadu, India: Three Decades of Experience - Sankaran, A.; Rajkumar, P. (Asian Business Review, 2014)
Industrial development plays a momentous role in all walks of development. The empirical investigations of world famous works pursued by Simon Kuznets(1966) Chennery(1980), Hoffman(1958), Murray & Bryce(1960) and Kaldor(1978) found that there is a positive and significant association between industrial development and overall development of a nation. In this paper an attempt is made to assess the various dimensions of industrial development of Tamil Nadu, India. To examine the performance of the industrial economy of Tamil Nadu, statistics have been collected from Annual Survey of Industries, published by Central Statistical Organization, Government of India. The variables administered in this work to evaluate the performance of agro based and non agro based manufacturing industries of Tamil Nadu include number of factories, productive capital, employment, value of output and value added. This study covers the period of three decades form 1980-81 to 2010-11, so as to understand the effects of the new economic policy. Further, the entire study period has been classified into two folds as pre reform period (1980-81 to 1990-91) and post reform period as (1991-92 to 2010-11). Collected statistics are deflated using wholesale price index to overcome the price fluctuation. The result obtained using annual compound growth rate reveals that almost all the variables express the same level of growth in both agro and non-agro related industries. But, owing to extraordinary performance of chemical based industries the value added of non- agro related industries reveal a dramatic growth. Mention should be made that the growth of employment has shown a negative sign during the reform period.   Hence, it is suggested that the policy makers should frame the effective and suitable policy considering the employment generation. Such kind of strategies will give a new life not only to India but also all the developing countries.
Keywords: Manufacture; India; Industrial Growth; Tamil Nadu